The Impact of Goiter and Thyroid Surgery on Goiter Related Esophageal Dysfunction. A Systematic Review - Sorensen, Jesper Roed; Bonnema, Steen Joop; Godballe, Christian; Hegedüs, Laszlo (Frontiers in Endocrinology, 2018)
Background: Patients with goiter referred for thyroidectomy report swallowing difficulties. This might be associated with esophageal compression and deviation as this is present in a significant number of patients. Studies on how goiter and subsequently its treatment affect the esophagus are sparse and point in various directions. Our aim was to investigate, through a systematic review, the impact of goiter and thyroidectomy on esophageal anatomy, esophageal physiology, and subjective swallowing dysfunction. Methods: The search period covered 1 January 1975 to 1 July 2018, using the scientific databases PubMed and EMBASE. Inclusion criteria were adult patients with goiter who were either observed or underwent thyroidectomy. Search terms were variations of the terms for goiter, esophagus, swallowing, and dysphagia. From an initial 3040 titles, 55 full text evaluations led to the final inclusion of 27 papers. Seventeen papers investigated, prospectively, the impact of thyroidectomy on the esophagus, while five observational and five retrospective studies were also included. Results: Esophageal anatomy impairment: Esophageal deviation occurred in 14% and esophageal compression in 8-27% of goiter patients. The prevalence increased with goiter size and with the extent of substernal extension. The smallest cross-sectional area of the esophagus increased by median 34% after thyroidectomy. Esophageal physiology changes: Goiter patients had increased esophageal transit time, positively correlated with goiter size, but unrelated to esophageal motility disturbances. Decrease in the upper esophageal sphincter pressure occurred early after surgery, and normalized within six months. Swallowing related patient-reported outcomes: Evaluated by validated questionnaires, swallowing symptoms worsened in the early period after thyroidectomy, but improved after six months, as compared to baseline. Conclusions: Thyroidectomy relieved patients with goiter from dysphagia, within 6 months of surgery probably via increase in the cross-sectional area of the esophagus. Attention to the impact by goiter on the esophagus is needed, and balanced and individualized information about the potential benefits and risks of thyroid surgery is crucial in the management of patients with goiter.